2015
DOI: 10.3171/2015.5.focus15157
|View full text |Cite
|
Sign up to set email alerts
|

Association of risk factors with unfavorable outcomes after resection of adult benign intradural spine tumors and the effect of hospital volume on outcomes: an analysis of 18, 297 patients across 774 US hospitals using the National Inpatient Sample (2002−2011)

Abstract: OBJECT Because of the limited data available regarding the associations between risk factors and the effect of hospital case volume on outcomes after resection of intradural spine tumors, the authors attempted to identify these associations by using a large population-based database. METHODS Using the National Inpatient Sample database, the authors performed a retrospective cohort study that involved pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Few studies have discussed healthcare utilization associated with intradural spinal tumors 14,15,24,41 as compared to multiple studies assessing costs in the treatment of metastatic epidural spinal cord compression. [25][26][27]42,43 Sharma et al 14 reported that the mean total hospital charges for treating intramedullary spine tumors in the National Inpatient Sample from 2003 to 2010 was $61 157.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have discussed healthcare utilization associated with intradural spinal tumors 14,15,24,41 as compared to multiple studies assessing costs in the treatment of metastatic epidural spinal cord compression. [25][26][27]42,43 Sharma et al 14 reported that the mean total hospital charges for treating intramedullary spine tumors in the National Inpatient Sample from 2003 to 2010 was $61 157.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies exist assessing efficacy, surgical approach, and complications associated with surgery for IDEM tumors. 5,[11][12][13][14][15] The estimated healthcare burden of treating patients with spinal disorders ranges from $80 to $100 billion. [16][17][18][19][20] Given the unsustainable cost of the current US healthcare system, value-based NEUROSURGERY VOLUME 81 | NUMBER 4 | OCTOBER 2017 | 613 Downloaded from https://academic.oup.com/neurosurgery/article-abstract/81/4/613/3813676 by guest on 08 June 2019 purchasing is being rapidly implemented.…”
mentioning
confidence: 99%
“…Previous studies have explored the volume-outcome relationship in the context of several neurosurgical procedures, [2][3][4][5][6]15,16,23,24,26,28,29,44,51,54 including those involving the spine. 17,20,28,42,43 For scoliosis surgery, Patil et al 41 defined 5 hospital surgical volume cutoffs ranging from < 21 operations per year to > 147 per year.…”
mentioning
confidence: 99%
“…17,20,28,42,43 For scoliosis surgery, Patil et al 41 defined 5 hospital surgical volume cutoffs ranging from < 21 operations per year to > 147 per year. Further, the authors investigated in-hospital mortality, discharge disposition, and complications following surgical correction.…”
mentioning
confidence: 99%
“…Clearly, where an insurance-dominated health care system does not provide financial cover for the subscriber's preferred treatment option of a proven noninferior procedure, demand for the procedure will be low (and this, in turn, will have implications for surgical volume and corollary adverse implications for retention of appropriate spinal surgical skills 674 ). And if the eligibility criteria for supporting the procedure are too restrictive and fail to reflect advances since the initial trials that have confirmed noninferiority of LTDR when compared with fusion, patient demand and surgical skills are adversely affected.…”
Section: Uptake By Spinal Surgeonsmentioning
confidence: 99%